The Burden of Care in Nasoalveolar Molding Treatment in Cleft Patients - Dominika Magyar; Bálint Nemes; Laura Pálvölgyi; Zoltán Pulay; Krisztián Nagy (Indian Journal of Plastic Surgery)
Objectives This study, first in Hungary, examined the success of presurgical nasoalveolar molding (NAM) therapy in cleft patients from a caregiver's perspective and revealed factors that can cause inconvenience. Patients and Methods A survey-based study was performed using a 32-item questionnaire following NAM therapy. The survey was sent to families whose child underwent NAM therapy from 2010 until 2020 at the 1st Department of Paediatrics, Semmelweis University. The questions focused on four main parts: socioeconomic, origin of the cleft, difficulties of therapy, and self-assessment. Fifty-three families received the questionnaire, 17 of them completed it. Results The mean age was 5 ± 3.7 weeks when NAM therapy started. Fifty-eight percent of the patients were male and 42% female. Patients are living more than 60 km from the cleft center (59%). Patients had to make the journey between their residence and the cleft center ∼10 to 15 times. In most cases, NAM therapy was covered by health insurance (83%). The unilateral cleft and lip palate occurred 58%, while the bilateral were 42%. Thirty-five percent of the patients had an allergic reaction against the adhesive, and 35% were affected by wounds on their lips or noses. The way of feeding was variable. Seventeen percent of the parents were able to breastfeed. In all cases, parents were satisfied with the NAM therapy. Conclusions The present study highlighted the value of caregivers' role in NAM therapy. The burden of care is acceptable, caregivers have high compliance, and are determined to help the effectiveness of therapy. Limitations of this study include a single-institute data with a small number of cases.